Using sound for stress therapy in a virtual-reality environment - Abdul Latif, Rubijesmin; Ismail, Rozita; Zainudin, Ahmad Redza Razieff (2015)
This paper discusses about comparing different sounds used in stress therapy among Malaysians. The aim of the stress therapy is to reduce stress among users, thus a virtual reality environment was used which replaces the traditional guided therapy sessions. Two groups were studied in the experiment; the first group - the therapies were guided by computer and sound types applied were instruction, natural sound and zikr. Meanwhile, the second group - sessions were also guided by computer but with different sound types (instructions, natural sound and instrumental music).The result of the experiment showed that the first group-guided with natural and zikr sound choice does have higher impact to positive emotions compared those exposed to natural and instrumental sound choice.